Agomelatine alleviates pain-related behaviour in ovariectomized rats (Annals of Medical Research, 2024)
Aim: Menopause is a physiological process that results in the cessation of ovarian follicle activity. Research suggests that postmenopausal women may experience changes in pain sensitivity. Ovariectomized (Ovx) rats are commonly used to mimic postmenopausal pain symptoms in research. Agomelatine is a unique antidepressant that acts as both a melatonergic receptor agonist and a 5-HT2C receptor antagonist. Preclinical studies have suggested potential analgesic effects associated with agomelatine. This study aims to investigate the influence of agomelatine on pain behavior in Ovx rats.Materials and Methods: Forty female Sprague Dawley rats were divided into four groups: Sham, Ovx, Ago20 and Ago40. The Ovx, Ago20 and Ago40 groups underwent bilateral ovariectomy, while the Sham group underwent all surgical procedures except ovarian ligation. After four months, the Sham and Ovx groups received vehicle, while the Ago20 (20mg/kg) and Ago40 (40mg/kg) groups received agomelatine by oral gavage for two months. Pain sensitivity assessments were conducted using electronic von Frey, hot plate, tail flick, and tail immersion methods after the final drug administration.Results: In the Ovx group, there was an increase in pain sensitivity observed in the hot plate, electronic von Frey, tail flick, and tail immersion tests (p < 0.05). Agomelatine treatment significantly reduced the heightened nociceptive response (p < 0.05).Conclusion: Agomelatine effectively attenuates the increased sensitivity to pain observed in Ovx rats.
Keywords: Agomelatine; Pain; Ovariectomy